The use of non-uniform drowning terminology: a follow-up study - Schmidt, AC (2017)
Background: In 2002, the World Congress on Drowning developed a uniform definition for drowning. The aim of this study is to determine the prevalence of “non-uniform drowning terminology” (NUDT) and “non-uniform drowning definitions” (NUDD) in peer-reviewed scientific literature from 2010 to 2016, and compare these findings with those from our unpublished study performing a similar analysis on literature from 2003 to 2010. Methods: A systematic review was performed using drowning-specific search terms in Pubmed and Web of Science. Titles and abstracts published between July 2010 and January 2016 were screened for relevance to the study focus. Articles meeting screening criteria were reviewed for exclusion criteria to produce the final group of studies. These articles were reviewed by four reviewers for NUDT and NUDD. The Fisher exact test was used to determine any statistically significant changes. Results: The final group of studies included 167 articles. A total of 53 articles (32%) utilized NUDT, with 100% of these including the term “near drowning”. The proportion of articles utilizing NUDT was significantly less than reported by our previous study (p < 0.05). In addition, 32% of the articles included a definition for drowning (uniform or non-uniform), with 15% of these utilizing NUDD. Discussion: Our study reveals a statistically significant improvement over the past thirteen years in the use of uniform drowning terminology in peer-reviewed scientific literature, although year-to-year variability over the current study period does not yield an obvious trend. Conclusions: Of the articles reviewed during the 2010-2016 study period, 32% included outdated and non-uniform drowning terminology and definitions. While this reveals an absolute decrease of 11% as compared with the previous study period (2003-2010), there is still significant room for improvement.